Pemanfaatan dan Penggunaan Secara Rasional Tanaman Obat Tradisional Sebagai Terapi Swamedikasi di Kampung KB, Magersari Kota Magelang - Ni Made Ayu Nila Septianingrum; Fitriana Yuliastuti; Widarika Santi Hapsari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
Self-medication (swamedikasi) is one of the ways that many people do to overcome the symptoms of the disease before getting help from the health center. Magersari village has 13 hamlets (RW) with a total population of 7.728 society and has the advantage as the hometown of family planning (KB). Most large residents in kampung KB magersari consume traditional drugs without knowing the appropriate doses. It supports the activities need of devotion is that people rationally in taking conventional medicine. The purpose of this service is to increase knowledge and skills about the use of plants environment around that have potential as a drug of mothers in kampung KB, magersari, Magelang. The method used participatory rural appraisal (PRA). The activity was carried out for three months by socialization to the head of kampung KB. Besides, a series of FGD activities, an increase of community capacity of kampung KB through training and practice to assist in implementing therapy swamedikasi. As a result, KB members received additional information about the properties and functions of Indonesia's natural plants partly already presented in the form of pocketbooks and presentations that can be used as one of the sources of information for swamedikasi. Besides, they were able to implement swamedikai to exploit and use traditional medicine through still in a simple form.